2007
DOI: 10.1007/s10620-006-9500-y
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-l-Glutamine, A Liquid-Stable Source of Glutamine, Partially Prevents Changes in Body Weight and on Intestinal Immunity Induced by Protein Energy Malnutrition in Pigs

Abstract: The goal of this study was to evaluate the preventive effect of free glutamine versus N-acetyl-L-glutamine, a liquid-stable source of glutamine, on gut damage induced by protein energy malnutrition in pigs. Healthy pigs (n = 6) were fed a liquid formula for 30 days. Three subgroups of malnourished pigs (n = 6) received daily 20% of the food intake recorded in control group, supplemented with calcium caseinate, glutamine, or N-acetyl-L-glutamine. Body weight was recorded, and small intestinal samples were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…This protein consists primarily of gliadin and glutenin, which are rich in glutamic acid and proline and are beneficial for the intestinal health of animals [ 11 ]. Previous studies have shown that fermentation of feed ingredients can increase the digestibility of amino acids [ 7 , 8 ], improve intestinal digestion capacity [ 12 ], promote daily gain, and increase feed intake [ 13 , 14 ]. Previous research showed that wheat protein can promote the growth of weaning piglets, is better than plasma protein and glutamine for improving piglet immunity, and can increase the daily gain and improve the feed efficiency in weaning piglets [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein consists primarily of gliadin and glutenin, which are rich in glutamic acid and proline and are beneficial for the intestinal health of animals [ 11 ]. Previous studies have shown that fermentation of feed ingredients can increase the digestibility of amino acids [ 7 , 8 ], improve intestinal digestion capacity [ 12 ], promote daily gain, and increase feed intake [ 13 , 14 ]. Previous research showed that wheat protein can promote the growth of weaning piglets, is better than plasma protein and glutamine for improving piglet immunity, and can increase the daily gain and improve the feed efficiency in weaning piglets [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies over the past 10 years have shown that glutamine and/or glutamate supplementation can be beneficial to recently weaned piglets ( Jiang et al, 2009 , López-Pedrosa et al, 2007 , Wang et al, 2008 , Wu et al, 1996 , Yi et al, 2005 , Yoo et al, 1997 ). Such studies have indicated benefits in preventing intestinal atrophy, maintaining anti-oxidant status and lessening the incidence of diarrhea, and result in increased weight gain and improved food efficiency.…”
Section: Glutamate and Glutaminementioning
confidence: 99%
“…Mitochondrial uptake of cytosolic NAG is not possible. Ingested NAG will be deacetylated like NAA by aminoacylase-1 and studies in rats, dogs and pigs with orally, enterally or parenterally administered N-acetylglutamine as a substitute for glutamine have shown that the nutritional value of Nacetylglutamine was comparable to that of L-glutamine (Neuhäuser-Berthold, et al, 1988;Gouttebel et al, 1992;Arnaud et al, 2004;Lopez-Pedrosa et al, 2007).…”
Section: Information On Naa and Nagmentioning
confidence: 99%